“Can Temperature and Pressure Change the Elasticity and Hooke’s Beyond Limit of Rubber Bands?” - Sharma, Om; Sharma, Dipti (European Journal of Applied Sciences, 2022)
In this report, a scientific research project is presented that is done for 2022 Massachusetts State Science Fair (MSEF) on rubber bands. This research work shows how the effect of temperature and pressure can change elasticity of the rubber bands those are found at home and used in everyday life. This work is done during COVID 19 time and shows how hands on activities can be performed to continue research work at home or in limited resources when it is not possible to go out very frequently. It is found after experimentation that rubber bands show more flexibility with lower spring constant and stop obeying Hooke’s Law on lower values of force applied to them under conditions of high pressure and temperature.